Incidental finding of supra cardiac total anomalous pulmonary venous connection with Tetralogy of Fallot: a case report - Khan, Mohammad Umair; Qureshi, Ahmad Usaid; Razzaq, Mujahid; Khan, Mohammad Asim (Journal of the Pakistan Medical Association, 2026)
Tetralogy of Fallot (TOF) is the most common cyanotic congenital heart disorder (CHD) worldwide and is known to be associated with a variety of other CHDs. This case report explores a rare incidental combination of TOF and supracardiac total anomalous pulmonary venous connection (TAPVC). Such a coexistence is exceedingly uncommon with only a handful of reported cases which prompts the need for documentation, especially its management in a developing country. Prompt diagnosis is challenging due to atypical symptoms which emphasises the importance of comprehensive imaging. Surgical intervention, guided by pre-operative cardiac catheterisation, addressed the anatomical complexities and facilitated successful single-stage repair. The patient was discharged on the fifth post-operative day. Follow-up echocardiogram demonstrated no residual ventricular septal defect, unobstructed right ventricular outflow, normal biventricular function, and unrestricted pulmonary venous drainage to the left atrium. Keywords: Congenital heart defect, Tetralogy of Fallot, TAPVC.